A relação avós-netos e o resgate do mundo vivido em vinculação com a literatura infantil. Repercussões na prática pedagógica. - Cechella, Leda Beatriz Romano dos Santos (2004)
This work fits the research live of educational practices in institutions, haring Education as the concentration area. The research approach is of qualitative feature and the study is based the phenomenology. While getting information, semi-structured interviews were used; in information interpretation, the content analysis process was used. In this study, information was colleted through direct contact between researcher and the researched subject. The chosen theme was: Grandfathers/grandmothers with the responsibility of bringing up their grandsons/grandfathers and the linking of this relationships with the juvenile literature: repercussions in the pedagogical practice of the juvenile education and beginning grades. This work aims at presenting a didactic – pedagogical proposal, with literary suggestions about the grandfather/grandmother, grandson/granddaughter relationship theme. Research subjects were five grandparents who brought up their grandchildren, taking the role of parents. Through these grandparents who, in fact, took this role without any choice, but inplenitude, it was investigated how they behaved and felt along the process, that is, their socio-emotional discovery is approached, by Erik Erikson”s Theory of Personality (1998). Not only the years that these relationships lasted and the influences that happened during this time were observed, but also the world lived by the grandparents. The importance of juvenile literature was highlighted at the encounter of the two generations: grandparents/ grandchildren, through the justification that it is complementary to the stories told by grandparents, whose speeches and narratives passed to their grandchildren, stories full of experience, rich in culture. A didactic-pegagogical inventory of the juvenile literature work whose theme focused the relationship grandparents/ grandchildren was done, so that such works, when read, helped strengthen ties between the two generations. In the last part of the research some juvenile literature works and the technics to tell stories, were classified, aiming at bringing grandfathers, grandmothers, grandsons, granddaughters near, with gentleness and pleasure, through reading and narrating in the educational environment.